2007
DOI: 10.1109/iembs.2007.4352809
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Study of Calorie-restricted Rats from Early Old Age

Abstract: These findings demonstrated that CR in early old rats delayed the declination of spatial cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
13
2
Order By: Relevance
“…For example, Means et al reported that 40% CR begun at 14-mo in C57BL/6Nnia mice attenuated age-related decline in grip strength, motor coordination, and spontaneous alternation behavior, but did not have significant effects on performance in the Morris water maze (MWM) (Means et al, 1993). Geng et al noted significant benefits to motor performance (open field) and cognition (MWM) as well as for survival in 18-mo old rats introduced to 40% CR for 6 months (Geng et al, 2007). Singh et al introduced an IF regimen (EOD) to 21-mo old male Wistar rats for 3 months and noted significant improvements in motor performance (rotarod test) and cognition (MWM) (Singh et al, 2012).…”
Section: At What Age Does Cr No Longer Produce Benefits?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Means et al reported that 40% CR begun at 14-mo in C57BL/6Nnia mice attenuated age-related decline in grip strength, motor coordination, and spontaneous alternation behavior, but did not have significant effects on performance in the Morris water maze (MWM) (Means et al, 1993). Geng et al noted significant benefits to motor performance (open field) and cognition (MWM) as well as for survival in 18-mo old rats introduced to 40% CR for 6 months (Geng et al, 2007). Singh et al introduced an IF regimen (EOD) to 21-mo old male Wistar rats for 3 months and noted significant improvements in motor performance (rotarod test) and cognition (MWM) (Singh et al, 2012).…”
Section: At What Age Does Cr No Longer Produce Benefits?mentioning
confidence: 99%
“…Kuhla et al reported improved learning and memory performance of 19-mo old mice begun on a regimen of 40% CR at weaning (Kuhla et al, 2013). Geng et al initiated 40% CR in 18-mo old rats and noted improved learning and memory in MWM performance at 24 mo (Geng et al, 2007). Similarly, Singh et al subjected 24-mo old male Wistar rats to EOD feeding for 3 mo and reported improved MWM in both the learning and memory phases of the task (Singh et al, 2012).…”
Section: Does Cr Attenuate Cognitive Decline?mentioning
confidence: 99%
“…Depending on the animal species examined, both decreases and increases in locomotor activity have been described in response to limited food supplies (Pirke et al, 1993;Weed et al, 1997;Geng et al, 2007;Teske and Kotz, 2009;Boehm et al, 2010;Gingerich et al, 2010;Yu et al, 2010). However, gait-specific effects have not been considered.…”
Section: Received 1 November 2013; Accepted 10 April 2014mentioning
confidence: 99%
“…In contrast, rats show hyperactive wheel running in response to starvation (Koubi et al, 1991;Pirke et al, 1993). Similarly, caloric restriction increases physical activity in rats (Geng et al, 2007;Teske and Kotz, 2009) and rhesus monkeys (Weed et al, 1997). It is of note that up to 80% of human patients with the eating disorder anorexia nervosa show excessive physical activity (Koubi et al, 1991;Hebebrand et al, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…It is common to restrict the consumption of food to motivate aged animals to look for the treats in the maze [221]. However, in the case of dietary interventions this may be a problem, especially because food restriction is reported to enhance spatial memory in aged rodents [72,166].…”
Section: Comparison Between the Radial Arm Maze And Morris Water Mazementioning
confidence: 99%